An Improved Spectral Subtraction Algorithm for Noise Reduction in Cochlear Implants with Increasing Number of Channels - Marjan Mozaffarilegha; Saeed Kermani (مجله دانشکده پزشکی اصفهان, 2013)
Background: Cochlear implants are widely accepted as the unique and most effective way for individuals with severe to profound hearing loss to restore some degree of hearing. Speech enhancement strategies play an extremely important role in optimizing the cochlear implant. In this study, a noise reduction algorithm was proposed for cochlear implant.